SOME ASPECTS OF THE PROBLEM SUFISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article explores key aspects of the emergence and development of Sufism (Tasawwuf) within Islamic history, focusing on its role in spiritual and moral education. It examines the significance of lataif (spiritual centers), the methods of dhikr (remembrance of God), the murshid-murid relationship, and the characteristics of major Sufi orders such as Naqshbandiyya and Yassawiyya. The paper also highlights the contribution of Turkestan’s Sufi traditions to the broader Islamic civilization and their integration with local culture and customs.
Keywords: Tasawwuf, Tariqa, Dhikr, Lataif, Murid, Murshid, Naqshbandiyya, Ahmad Yassawi, spiritual training.